Power and Legitimacy in International Politics: Britain and Germany’s Responses to the U.S.’s Wars Against Iraq in 1991 and 2003 - Afrimadona Afrimadona (Institute of International Studies, 2014)
The paper evaluates the constructivist claim that legitimacy embedded in a country’s foreign policy shapes the responses of other countries’ foreign policy. I test the claim using four cases of Britain’s and Germany’s responses to US’s invasion in Iraq in 1991 and 2003. The choice of US’s invasion in Iraq in 1991 and 2003 was made on the ground that the latter was regarded as utterly illegitimate due to a lack of UN’s authorization. Thus, both cases reveal a variation in the extent of legitimacy (positive versus negative cases). My observation of Britain’s and Germany’s foreign policy responses is based on the fact that both countries are US’s allies. Thus, by examining allies’ responses to US’s invasion in Iraq in these two periods, I control for countries’ type of relationship with the US that may affect their behavior towards the country. My observation shows that only one out of the four cases (Germany’s response to US’s invasion in 2003) supports the claim that legitimacy is the main concern underlying states’ foreign policy response. In general, this study also suggests that legitimacy may matter under normal situation. During crises, however, states tend to be more pragmatic and power-based explanation seems more convincing.